Knock-down of circular RNA H19 induces human adipose-derived stem cells adipogenic differentiation via a mechanism involving the polypyrimidine tract-binding protein 1 - Zhu, Yiyi; Gui, Weiwei; Lin, Xihua; Li, Hong (Experimental cell research, 2020)
The metabolic syndrome (MetS) is characterized of a cluster of medical disorders. Altered function of adipose tissue has a significant impact on whole-body metabolism and represents a key driver for MetS. In this study, we aim to explore the function of human circular RNA H19 (hsa_circH19) in human adipose-derived stem cells (hADSCs). The blood samples from MetS patients and normal subjects were used to determine the expression level of the hsa_circH19. After knock-down of hsa_circH19 in hADSCs, we measured the expression of adipogenic genes. Oil red O, Nile red staining assay and triglyceride assessment were performed to examine the role of hsa_circH19 in hADSCs differentiation. Then, RNA Pull-down and RIP assays were conducted to explore the related RNA binding protein of hsa_circH19. IF was performed to determine the potential molecular regulatory mechanism. After accounting for confounding factors, high levels of hsa_circH19 remained an independent risk factor for MetS. Furthermore, the knockdown of hsa_circH19 significantly increased the expression of adipogenic genes and the formation of lipid droplets. Bioinformatics analyses revealed that has_circH19 shared multiple binding sites with polypyrimidine tract-binding protein 1 (PTBP1) and their interaction was validated by circRNA pull-down and RIP assays. Mechanistically, depletion of hsa_circH19 triggered translocation of sterol-regulatory element binding proteins (SREBP1) from cytoplasm to nucleus in the presence of PTBP1. Our experiments suggest that knockdown of hsa_circH19 promotes hADCSs adipogenic differentiation via targeting of PTBP1. In consequence, the expression of hsa_circH19 might correlated to lipid metabolism in adipose tissue from MetS.